Pengaruh Kepemimpinan, Motivasi dan Komitmen Organisasi terhadap Kinerja Kelompok Tani di Desa Grogol Kecamatan Grogol - Imanudin, M.Handik; Meilina, Restin; Sardanto, Rino (Lembaga Yasin AlSys, 2023)
The agricultural sector in the industrial world, both food and textiles, is very important to support progress and the country’s need for food and textile staples. Where this can help economic growth is in the provision of employment, as a supplier of industrial raw materials such as food and textiles to other countries as well as the country itself. The research question is: “Does leadership, motivation, and organizational commitment affect the success of farmer groups in Grogol Village?” In this study, the population used to determine the population was all members of the Farmers’ Group in Grogol Village, totaling 40 individuals. A saturated sample, often known as a census, is one in which all members of the population are included. A sample of the population is taken. Leadership, motivation, and organizational commitment are known to have a significant influence, partially and simultaneously, on the performance of farmer groups in Grogol Village. According to the findings of this study, leaders must be more accountable in carrying out their responsibilities, and members must be more responsible in their organizations.